(untitled) (Leadership, Education, Personality: An Interdisciplinary Journal, ISSN: 2524-6178, 2025)
Of many other forms of art, literature is a special type of art as it takes human life as its main theme. Broadly, from creative writing to more technical or scientific works, all writings fall under the head of the term ‘literature’ but most commonly it is used to refer to works of the creative imagination, embracing works of poetry, drama, fiction and non-fiction. The writing that is recognised for its artistic quality and has passed the test of time is generally literature. In its various forms, figurative or critical, literature has become a way in life for all human beings to gather other forms of information. Literature was earlier taken for just an art form, used for expression, a mere play of imagination, pleasing enough, but far from any serious or practical importance. But now it is considered as powerful equipment in the hands of creative writers to reflect the reality, even the grimmer side of life and by that means fight against the established social norms and hypocritical reactions, outmoded customs, traditions, and the political system. It is now considered as a means to modulate and change the societal framework, as something that preserves the cultural ideals of a people—some of these ideals being love, beauty, truth, faith, duty, friendship, loyalty, freedom, reverence. Upon these ideals, rest our whole civilization, our development, our world, our religion, our culture, our freedom. In fact the growth of literature and the growth of human civilization are inter-related. Thus human society and culture are naturally related to literature.